2012
DOI: 10.1111/j.1365-2559.2012.04199.x
|View full text |Cite
|
Sign up to set email alerts
|

Nodal cytotoxic molecule (CM)‐positive Epstein–Barr virus (EBV)‐associated peripheral T cell lymphoma (PTCL): a clinicopathological study of 26 cases

Abstract: Kato S, Takahashi E, Asano N, Tanaka T, Megahed N, Kinoshita T & Nakamura S 
(2012) Histopathology 61, 186–199 Nodal cytotoxic molecule (CM)‐positive Epstein–Barr virus (EBV)‐associated peripheral T cell lymphoma (PTCL): a clinicopathological study of 26 cases Aims:  The clinicopathological distinctiveness of nodal cytotoxic molecule (CM)‐positive Epstein–Barr virus (EBV)‐associated peripheral T cell lymphoma (PTCL) remains to be clarified. We investigated 26 patients with this lymphoma compared to nodal CM+ E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 51 publications
5
61
0
1
Order By: Relevance
“…Thus, we preferred EBV-positive nodal T/NK-cell lymphoma to nodal involvement of extranodal lymphoma in these patients. In addition, because EBV-positive cells have been encountered in variable proportions in EBV-positive nodal T-cell lymphomas, we adopted a threshold of EBV positivity of at least 30% of neoplastic cells, in accordance with a recent study [8]. In fact, all cases in our study showed unequivocal EBV positivity ranging from 40% to 80% of tumor cells.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Thus, we preferred EBV-positive nodal T/NK-cell lymphoma to nodal involvement of extranodal lymphoma in these patients. In addition, because EBV-positive cells have been encountered in variable proportions in EBV-positive nodal T-cell lymphomas, we adopted a threshold of EBV positivity of at least 30% of neoplastic cells, in accordance with a recent study [8]. In fact, all cases in our study showed unequivocal EBV positivity ranging from 40% to 80% of tumor cells.…”
Section: Discussionmentioning
confidence: 50%
“…Although the existence of EBV-positive nodal T/NK-cell lymphoma has been recognized by many hematopathologists [3,8,9,[12][13][14], only a few case series are available on this disease; therefore, the clinicopathological characteristics of EBV-positive nodal T/NK-cell lymphoma remain to be clarified. This paucity might be attributable to the rarity of EBV-positive nodal T/NK-cell lymphoma and the lack of consensus criteria for the diagnosis of EBV-positive nodal T/NK-cell lymphoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in recent years, nodal cytotoxic molecule-positive and EBV-associated PTCL-NOS has been supposed to be distinct from the current category of mature T/natural killer (NK) cell lymphomas, because of its unique immunophenotypes and aggressive clinical course (9). The present case, therefore, would be categorized into this type of PTCL-NOS, due to its similar phenotype and clinical picture, although our case was an extra-nodal type.…”
Section: Discussionmentioning
confidence: 78%
“…Приблизительно в четверти слу-чаев ЭНКТЛ может наблюдаться поражение костного мозга и лейкемизация опухолевого процесса [15]. Пер-вичное поражение лимфатических узлов (ЛУ) без экс-транодальных поражений при ЭНКТЛ встречается крайне редко, в таких случаях необходимо проводить дифференциальную диагностику с цитотоксической нодальной Т-клеточной лимфомой, ассоциированной с вирусом Эпштейна-Барр (ВЭБ) [16].…”
Section: Introductionunclassified